Lorena isang tulambuhay - Hernando, Pauline Mari; University of the Philippines Press (Quezon City University of the Philippines Press, 2018)
Biography of Maria Lorena Barros, an activist during the Martial Law in the Philippines and founding MAKIBAKA, a militant women's organization, was killed during a military ambush at 28 years old.
Includes bibliographical references (pages 249-252)
Keywords: Barros, Maria Lorena -- 1948-1976.; Women political activists -- Philippines -- Biography